The impact of design thinking on the learning of basketball and badminton - Nazar Kzar, Muhannad; Yaseen Alwan, Ali; Salim Hamza, Dhay (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study investigated the impact of the design thinking strategy on students’ acquisition, learning, and maintenance of basketball and badminton skills. Using an experimental method, researchers compared two groups: an experimental group (Group A) that utilized the design thinking strategy and a control group (Group C) that used traditional teaching. The sample consisted of 58 third-year students from the Faculty of Physical Education and Sports Sciences at Al-Mustaqbal University, representing both groups. The acquisition test, prepared by the researchers, covered comprehension, interpretation, and application of concepts. It followed the same lesson sequence as the control group. Pre-existing basketball and badminton skills tests from the Hilla College curriculum were used. Statistically significant differences were found between the experimental and control groups, with the experimental group outperforming the control group in both the acquisition (p < 0.05) and maintenance tests (p < 0.05). The design thinking strategy effectively enhances the acquisition and maintenance of basketball and badminton skills compared to traditional methods. It also increases student engagement by fostering active participation, discussions, and creative problem-solving.